Transformation mechanisms of tetracycline by horseradish peroxidase with/without redox mediator ABTS for variable water chemistry. (November 2020) - Leng, Yifei; Bao, Jianguo; Xiao, Henglin; Song, Dandan; Du, Jiangkun; Mohapatra, Sanjeeb; Werner, David; Wang, Jun
Abstract: The threat of antibiotics in the environment causing antibiotics resistance is a global health concern. Enzymes catalyze pollutant transformations, and how commercially available enzymes like horseradish peroxidase (HRP), with or without a redox mediator, may be used to degrade antibiotics in water treatment is of great interest. This work demonstrates tetracycline transformation by HRP, and how it is significantly enhanced by free radicals created from the mediator 2, 2-Azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS). Water temperature and pH strongly inﬂuence the tetracycline removal rate due to their correlation with the enzyme activity, abundance and stability of ABTS + . Four transformation products were identified in the pure HRP system using a liquid chromatography tandem mass spectrometry hybrid quadrupole-orbitrap mass spectrometer system. Addition of 25 μmol L −1 ABTS not only accelerated the degradation of tetracycline, but also expanded the range of degradation pathways. Potential tetracycline transformation pathways are proposed based on these observations, which include a range of mechanisms such as hydroxylation, demethylation, dehydration, decarbonylation and secondary alcohol oxidation. Despite of decreased efficiency, the HRP/ABTS system was able to degrade tetracycline in a domestic wastewater treatment plant effluent matrix, which demonstrates the potential of the system to be utilized in wastewater treatment. Graphical abstract: Image 1 Highlights: Temperature and pH influenced the removal of tetracycline by HRP and HRP/ABTS. The highly reactive ABTS. + accelerated tetracycline removal in the HRP/ABTS system. ABTS. + could expand the tetracycline transformation pathways by additional products. The HRP/ABTS system has potential in industrial wastewater treatment.